2009
DOI: 10.1007/s12217-009-9154-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gravity and Shear Stress on a Liquid Film Driven in a Horizontal Minichannel at Local Heating

Abstract: The present study is focused on the investigation of gravity effect on thermocapillary deformations in a film flowing under action of co-current gas flow, which creates the tangential force on the gas-liquid interface. The influence of local heating intensity on the heater at a substrate is also investigated. Effects of surface tension, temperature dependent viscosity and thermocapillarity are taken into account. Investigations have shown that gravity has a significant effect on the film deformations and patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…6. These results are in good agreement with numerical results obtained in Kabova et al (2009) where the gravity effect on thermocapillary deformations in a film flowing under the action of co-current gas flow in a horizontal minichannel has been investigated for the case of no evaporation taken into account. It was shown that decreasing the gravity level leads to a flow destabilization; particularly, a middle stream between two main lateral waves exists at the low gravity conditions.…”
Section: Thermocapillary Deformations and Temperature Distributionsupporting
confidence: 89%
“…6. These results are in good agreement with numerical results obtained in Kabova et al (2009) where the gravity effect on thermocapillary deformations in a film flowing under the action of co-current gas flow in a horizontal minichannel has been investigated for the case of no evaporation taken into account. It was shown that decreasing the gravity level leads to a flow destabilization; particularly, a middle stream between two main lateral waves exists at the low gravity conditions.…”
Section: Thermocapillary Deformations and Temperature Distributionsupporting
confidence: 89%
“…Experimental studies were conducted as presented in a series of papers mostly in collaboration with V. Cheverda, Y. Lyulin, and D. Zaitsev, while theoretical and numerical work was done by E. Gatapova (Gatapova and Kabov, 2008) and Yu. Kabova (Kabova et al, 2009). In particular, the pioneering study of Gatapova and Kabov (2008) was the first to incorporate the effects of evaporation due to the presence of localized heating into a mathematical model of shear-driven film.…”
Section: Figmentioning
confidence: 99%
“…A liquid bump caused by the thermocapillary force was obtained just above the heated zone. Kabova et al (2008Kabova et al ( , 2009 investigated the thin non-isothermal liquid film flowing down by gravity and co-current gas flow in an inclined minichannel. They developed 3D time-dependent mathematical model.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%